2016
DOI: 10.1038/ncomms12382
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalysed formation of vicinal all-carbon quaternary centres via propargylation

Abstract: Construction of two vicinal all-carbon quaternary carbon centres is of great importance due to the common presence of such units in natural and unnatural molecules with attractive functions. However, it remains a significant challenge. Here, we have developed a palladium-catalysed general coupling for the efficient connection of two tertiary carbon atoms: Specifically, propargylic carbonate has been treated with a fully loaded soft functionalized nucleophile to connect such two fully loaded carbon atoms with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…In 2016, Ma and co-workers demonstrated the palladiumcatalyzed propargylic substitution of internal alkyne-containing propargylic carbonates with malononitrile derivatives for the formation of vicinal all-carbon quaternary centers. [21] In this study, the authors showed that the stereospecific propargylic alkylation of the propargylic carbonates with malononitriles also proceeded under the palladium catalysis to give the chiral alkylation products bearing two vicinal all-carbon quaternary centers in 79-90% yields without loss of enantiomeric purity of the starting materials (Scheme 10).…”
Section: Palladium Catalysismentioning
confidence: 95%
See 1 more Smart Citation
“…In 2016, Ma and co-workers demonstrated the palladiumcatalyzed propargylic substitution of internal alkyne-containing propargylic carbonates with malononitrile derivatives for the formation of vicinal all-carbon quaternary centers. [21] In this study, the authors showed that the stereospecific propargylic alkylation of the propargylic carbonates with malononitriles also proceeded under the palladium catalysis to give the chiral alkylation products bearing two vicinal all-carbon quaternary centers in 79-90% yields without loss of enantiomeric purity of the starting materials (Scheme 10).…”
Section: Palladium Catalysismentioning
confidence: 95%
“…As we mentioned in section 2.2.2, Ma and co-workers reported the palladium-catalyzed propargylic substitution of internal-alkyne substituted propargylic carbonates with soft carbon nucleophiles including its stereospecific variants. [21] The authors showed the scope of the non-asymmetric propargylic alkylation of the propargylic carbonates as shown in Scheme 45. A broad range of the tertiary propargylic carbonates and malononitrile derivatives engaged in the palladium catalysis, producing the desired alkylation products bearing vicinal allcarbon quaternary centers in up to 99% yield.…”
Section: Palladium Catalysismentioning
confidence: 99%
“…In 2000, thiolate-bridged diruthenium complexes as bioinspired catalysts were reported to catalytically promote propargylic substitution reactions of propargylic alcohols bearing a terminal alkyne moiety with various carbon- and heteroatom-centered nucleophiles to give the corresponding propargylic substituted products in good to high yields with complete selectivity. In this reaction system, ruthenium–allenylidene complexes were found to work as key reactive intermediates. , After our milestone work, a variety of transition-metal-catalyzed propargylic substitution reactions of propargylic alcohol derivatives were reported by many research groups. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kawatsura et al made seminal contribution in their design of nickel-catalyzed asymmetric Friedel-Crafts propargylation of 3-substituted indoles with propargylic carbonates 25 . However, efficient methods that achieve enantioselective control of the formation of C(sp 3 )-C(sp 3 ) bonds adjacent to internal alkynes with malonate derivatives have not been identified [26][27][28][29][30][31][32] . In light of the synthetic value of the reaction products, we embarked on the study to address the synthetic challenge and accomplish the enantioselective collective synthesis.…”
mentioning
confidence: 99%